PCSK9 inhibitor and atorvastatin reduce cardiac impairment in ovariectomized prediabetic rats via improved mitochondrial function and Ca2+ regulation - Patchareeya Amput (2020)
© 2020 The Authors. Journal of Cellular and Molecular Medicine published by Foundation for Cellular and Molecular Medicine and John Wiley & Sons Ltd Post-menopausal women have a higher risk of developing cardiometabolic dysfunction. Atorvastatin attenuates dyslipidaemia and cardiac dysfunction but it can have undesirable effects including increased risk of diabetes and myalgia. Currently, the proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor efficiently reduces low-density lipoprotein cholesterol (LDL-C) levels more effectively than atorvastatin. We have been suggested that PCSK9 inhibitor attenuated cardiometabolic impairment more effectively than atorvastatin in ovariectomized prediabetic rats. Female Wistar rats (n = 48) were fed a normal diet (ND) or high-fat diet (HFD) for 12 weeks. Then, HFD rats were assigned to a sham-operated (Sham) or ovariectomized (OVX) group. Six weeks after surgery, the OVX group was subdivided into 4 treatment groups: vehicle (HFOV), atorvastatin (HFOA) (40 mg/kg/day; s.c.), PCSK9 inhibitor (HFOP) (4 mg/kg/day; s.c.) and oestrogen (HFOE2) (50 µg/kg/day; s.c.) for an additional 3 weeks. Metabolic parameters, cardiac and mitochondrial function, and [Ca2+]i transients were evaluated. All HFD rats became obese-insulin resistant. HFS rats had significantly impaired left ventricular (LV) function, cardiac mitochondrial function and [Ca2+]i transient dysregulation. Oestrogen deprivation (HFOV) aggravated all of these impairments. Our findings indicated that the atorvastatin, PCSK9 inhibitor and oestrogen shared similar efficacy in the attenuation in cardiometabolic impairment in ovariectomized prediabetic rats.